Beauty Revealed - Sarah Goodridge (Wikimedia Commons, 1828)
Notice iconographique issue de Wikimedia Commons. Titre: Beauty Revealed. Beauty Revealed, a self-portrait by Sarah Goodridge
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures